Environmental Science and Management Datasets
DOI: 10.15760/esm-data.1
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic Concentrations in Two Oregon Bivalve Species: Spatial, Temporal, and Species Variability

Abstract: Microplastics are an ecological stressor with implications for ecosystem and human health when present in seafood. We quantified microplastic types, concentrations, anatomical burdens, geographic distribution, and temporal differences in Pacific oysters (Crassostrea gigas) and Pacific razor clams (Siliqua patula) from 15 Oregon coast, U.S.A. sites. Microplastics were present in organisms from all sites. On average, whole oysters and razor clams contained 10.95 ± 0.77 and 8.84 ± 0.45 microplastic pieces per ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 42 publications
0
18
1
Order By: Relevance
“…Fragments made up the majority of MPs counted (77–88%), followed by fibers (7–15%), and beads (1–8%). This contrasts with studies that have predominantly found anthropogenic fibers in oyster tissue [ 14 , 15 , 31 ]. However, most of these studies employed optical microscopy for detection instead of fluorescence microscopy, targeting larger microplastics.…”
Section: Resultscontrasting
confidence: 77%
See 1 more Smart Citation
“…Fragments made up the majority of MPs counted (77–88%), followed by fibers (7–15%), and beads (1–8%). This contrasts with studies that have predominantly found anthropogenic fibers in oyster tissue [ 14 , 15 , 31 ]. However, most of these studies employed optical microscopy for detection instead of fluorescence microscopy, targeting larger microplastics.…”
Section: Resultscontrasting
confidence: 77%
“…Moreover, whether the MPs are actually entrained in oyster tissues likely depends on their size and morphologies and whether they are ingested or just make contact with the tissues (see microplastic morphologies below). Recent studies on oyster ingestion of MPs have shown that oysters are ingesting and retaining between 0.6 and 16.5 MPs per individual [ 14 , 15 , 28 , 29 , 30 , 31 ]. These studies also show that oysters nearer urban centers often contained higher concentrations of MPs.…”
Section: Resultsmentioning
confidence: 99%
“…The carapace was peeled back and the number of acanthocephalan parasites (Profilicollis altmani) was recorded, as this parasite slows the sand crabs' burrowing speed to increase predation of the intermediate host by the definitive host, shore birds (Kollaru et al 2011). Then each crab was digested in a 10% KOH solution for 24 h at 40 C (Rochman et al 2016;Baechler et al 2019). The solution was filtered through a 63 μm steel mesh, then the residue was transferred into a glass petri dish triple-rinsed with filtered deionized water, and examined under a 10× Leica dissecting microscope to determine whether the yellow polypropylene fibers had been ingested.…”
Section: Assessment Of Microplastic Internalization By E Analogamentioning
confidence: 99%
“…Microplastic fibers are often the most dominant morphology reported in bivalves. For example, fibers accounted for 80% of microplastics in mussels (Mytilus edulis, Perna viridis) from China (Qu et al 2018), 90% of microplastics in Manila clams (V. philippinarum) from British Columbia (Davidson and Dudas 2016), and 99% in razor clams (Siliqua patula) and Pacific oyster (Crassostrea gigas) from Oregon, USA (Baechler et al 2020a). One of the hypotheses behind the observed high abundance of this type of microplastic is that fibers are likely harder to remove from digestive tracts.…”
Section: Microplastic In Bivalvesmentioning
confidence: 99%
“…Microplastics exposure in finfish is largely a result of plastics being mistaken for natural prey items, via ingestion of contaminated prey items or by passive uptake through gills (Lusher et al 2016;Watts et al 2015;Nelms et al 2018;Roch et al 2020). Trophic transfer of microplastics may also expose predaceous fish to microplastics (Farrell and Nelson 2013;Setälä et al 2014;Lusher et al 2016;Baechler et al 2020a), and microplastics have frequently been detected in finfish gastrointestinal tracts (e.g., Lusher et al 2017b,). The methodological challenges with identifying particles within fillet muscle tissue have limited the number of published studies thus far, although they have been identified albeit at extremely low concentrations (Zeytin et al 2020).…”
Section: Microplastics In Finfishmentioning
confidence: 99%